Trivalent cerium-preponderant CeO2/graphene sandwich-structured nanocomposite with greatly enhanced catalytic activity for the oxygen reduction reaction. Issue 14 (22nd March 2017) - Yu, Yu; Wang, Xiaofang; Gao, Wenyu; Li, Pei; Yan, Wei; Wu, Songmei; Cui, Qiuhong; Song, Weiguo; Ding, Kejian
Abstract : A sandwich-structured CeO2 /graphene nanocomposite was synthesized with enhanced ORR electrocatalytic activity due to large amounts of Ce(iii ) in the thin CeO2 crystalline film. Abstract : A sandwich-like CeO2 /graphene nanocomposite (CeGS) with a uniform thin CeO2 crystalline film coating on reduced graphene oxide is presented. Large amounts of trivalent Ce and abundant oxygen vacancies (VO ) were introduced onto the surface of CeGS. Due to the advantageous surficial crystal configuration, this CeGS displayed greatly enhanced catalytic activity and excellent durability for the oxygen reduction reaction (ORR). By DFT calculations, it was demonstrated that the Ce(iii )-preponderant and VO -containing surface benefited the intense chemical adsorption and activation of O2 and optimized the intermediate reaction pathways.